Chi's sweet home. 4 - Konami, Kanata, 1958- (Vertical, Inc., 2010)
Follows the adventures of Chi, a mischievous kitten who is adopted by Yohei and his family, the Yamadas, even though their lease explicitly states pets are not allowed in their building.